Measuring Awareness of the Importance of Green Computing Among Indonesian Senior High School Students: A Sample Study of One School - Rio Rinaldi; Fayyaz Haqqani; Dhafa Hibrizi Sitorus (Raskha Media Group, 2025)
Green computing socialization was conducted at SMK Muhammadiyah 8 Medan on May 31, 2025, to enhance student awareness regarding environmentally friendly technology practices. The primary issue addressed was the need to build a collective responsibility towards the environment within the school's digital culture. The purpose of this study is to measure the level of student awareness and evaluate the effectiveness of the education program which utilized lectures, demonstrations, and interactive discussions. The research method used is descriptive with a participatory approach, collecting data through observation and questionnaires. The results indicated a significant improvement in understanding among the 27 participants, with 8 participants responding